2016
DOI: 10.1080/13803395.2016.1264575
|View full text |Cite
|
Sign up to set email alerts
|

Elevated rates of memory impairment in military service-members and veterans with posttraumatic stress disorder

Abstract: Patients with PTSD were more likely to meet criteria for memory impairment and to show impairment in any domain than controls. Patients with PTSD and comorbid depression were no more likely to be impaired in any cognitive domain or to have lower scores on individual cognitive tasks than patients with PTSD alone. Clinicians noting cognitive impairment in individuals with PTSD should exercise caution before ascribing that impairment to another etiology if deficits are limited to memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 85 publications
2
22
0
1
Order By: Relevance
“…However, a small percentage of individuals report symptoms many months or years postinjury; these are often the result of a variety of non–brain injury–related factors and comorbidities that are commonly found pre‐ and postinjury (Iverson, Silverberg, Lange, & Zasler, ; McCrae, ). For military personnel, one of the most common and potentially debilitating comorbidities that occurs with mTBI is posttraumatic stress disorder (PTSD; Gates et al., ), which has been shown to increase the risk of neurocognitive and neurobehavioral deficits (Stricker et al., ), suicidality (Lemaire & Graham, ), and neuronal inflammation (Devoto et al., ). When PTSD occurs concurrently with mTBI, there may be additional psychological and/or neurobiological complications that are not attributable to brain insult alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a small percentage of individuals report symptoms many months or years postinjury; these are often the result of a variety of non–brain injury–related factors and comorbidities that are commonly found pre‐ and postinjury (Iverson, Silverberg, Lange, & Zasler, ; McCrae, ). For military personnel, one of the most common and potentially debilitating comorbidities that occurs with mTBI is posttraumatic stress disorder (PTSD; Gates et al., ), which has been shown to increase the risk of neurocognitive and neurobehavioral deficits (Stricker et al., ), suicidality (Lemaire & Graham, ), and neuronal inflammation (Devoto et al., ). When PTSD occurs concurrently with mTBI, there may be additional psychological and/or neurobiological complications that are not attributable to brain insult alone.…”
mentioning
confidence: 99%
“…E-mail: cassie.pattinson@nih.gov C 2019 International Society for Traumatic Stress Studies. View this article online at wileyonlinelibrary.com DOI: 10.1002/jts.22418 the risk of neurocognitive and neurobehavioral deficits (Stricker et al, 2017), suicidality (Lemaire & Graham, 2011), and neuronal inflammation (Devoto et al, 2017). When PTSD occurs concurrently with mTBI, there may be additional psychological and/or neurobiological complications that are not attributable to brain insult alone.…”
mentioning
confidence: 99%
“…Many previous studies of PTSD and cognitive function were carried out in populations of military veterans (16,34,35); however, a connection between PTSD and cognitive impairment has also been observed in studies of individuals exposed to other types of trauma (12,13,36), as well as in one study involving a general population (14). In the previously noted cohort of non-FDNY WTC responders, PTSD symptoms were associated with an increased risk of cognitive impairment (15).…”
Section: Discussionmentioning
confidence: 95%
“…Age, depression, and certain socioeconomic factors are well-established risk factors for cognitive impairment and dementia (9)(10)(11). Previous studies have also found post-traumatic stress disorder (PTSD) to be associated with reduced cognitive function (12)(13)(14) and deficits in multiple cognitive domains (12,15,16). Notably, PTSD earlier in life has been linked to worse cognitive performance in later years (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…However, our study population consists of military service members and their dependents, which may differ from the general population. This population is associated with higher rates of mental disorders, including posttraumatic stress disorder, major depressive disorder, bipolar disorder, memory impairment, and generalized anxiety disorder [31][32][33]. This setting may have allowed us to identify differences between the cohorts that would otherwise have remained undetected.…”
Section: Discussionmentioning
confidence: 99%